Understanding the Challenges in Financing Affordable Housing: Multiple Stakeholder Perspectives from Namibia - Nghifindaka, Twapandula (Graduate School of Business (GSB), 2021)
A stark worldwide reality is that there is a shortage of affordable housing, which is a fundamental economic indicator and key to addressing social policy objectives including poverty reduction. Post-independence, housing in Namibia has been classified a national priority, and as such, the government has passed legislation in favour of committing to housing delivery. The housing demand continues to outstrip the supply, and this is further intensified by urbanisation, high unemployment in the country, high house prices, and a shortage of serviced land. Resultantly, the Namibian government is continually targeting to increase land supply and to incentivise the private sector. This research was centred on the challenges faced by multiple stakeholders that are challenged with financing affordable housing. The stakeholders included a private equity fund manager tasked with a mandate of providing affordable residential property, property developers, and beneficiaries of affordable housing (homeowners). The efforts in support of affordable housing finance are not solely limited to end-user housing finance (e.g. mortgage financing), but additionally include the implementation of the housing value chain, including the land acquisition process, title deed registrations and transfers, and the construction process. The mortgage market is focused on the middle and higher-income market segments. Some financial institutions offer products that do not require down payments. Despite this, many Namibians cannot access loan financing due to affordability, bureaucratic processes, high indebtedness and lack of education about the mortgage process. Therefore, this study undertook to understand the challenges in financing affordable housing covering three main stakeholders: a fund manager, developers and homeowners. This study employed a qualitative approach to analyse data from the fund manager and developers while the sequential explanatory mixed-method approach was used to analyse the data from homeowners. From the analysis, we identified the challenges pertaining to the fund manager to be the length of land titling and registration process, acquisition of unserviced land from local authorities, the reliance of funding from single investor participants, and end-user financing bureaucracy (mortgage financers). The challenges faced by the developers were found to be linked to land acquisition, funding acquisition, building plan approvals, as well as other issues such as the high cost of building materials. The homeowner challenges were identified from the quantitative analysis as the lengthy bank application process, associated costs, and lengthy approval processes. From the qualitative analysis, the challenges identified pertained to the lengthy application processes at the financial institutions, the associated costs and lengthy bureaucratic approval processes. Based on the findings, the research proposed the need for increased engagement and negotiations to lift the stringent conditions placed by local authorities in order to provide serviced land for the purposes of affordable housing; the availing of additional capital to fund managers; the revision of the systems used in order to shorten the time it takes to register and transfer properties; in addition to the lengthy, bureaucratic, and stringent bank requirements and processes.